Cardiorespiratory Effects of Air Pollution in a Panel Study of Winter Outdoor Physical Activity in Older Adults. Issue 8 (August 2018) - Stieb, David M.; Shutt, Robin; Kauri, Lisa Marie; Roth, Gail; Szyszkowicz, Mieczyslaw; Dobbin, Nina A.; Chen, Li; Rigden, Marc; Van Ryswyk, Keith; Kulka, Ryan; Jovic, Branka; Mulholland, Marie; et al.
Abstract : Objective: The aim of this study was to assess cardiorespiratory effects of air pollution in older adults exercising outdoors in winter. Methods: Adults 55 years of age and older completed daily measurements of blood pressure, peak expiratory flow and oximetry, and weekly measurements of heart rate variability, endothelial function, spirometry, fraction of exhaled nitric oxide and urinary oxidative stress markers, before and after outdoor exercise, for 10 weeks. Data were analyzed using linear mixed effect models. Results: Pooled estimates combining 2014 ( n = 36 participants) and 2015 ( n = 34) indicated that an interquartile increase in the Air Quality Health Index was associated with a significant ( P < 0.05) increase in heart rate (0.33%) and significant decreases in forced expiratory volume (0.30%), and systolic (0.28%) and diastolic blood pressure (0.39%). Conclusion: Acute subclinical effects of air pollution were observed in older adults exercising outdoors in winter. Abstract : Supplemental Digital Content is available in the text